Conceptual study on hydrogen powered bicycle - Mohammad Nazree, Abd Malek (2013)
Nowadays, many companies are struggling in producing cleaner energy in order to overcome the oil depletion problem. Of late, the use of hydrogen has become a hot topic discussed among inventers as it has the ability to assist as well as posses the potential in becoming a new form of alternative source for transportation. In this thesis, a conceptual study of a hydrogen powered bicycle by using fuel cell technology is studied. In this study, a small hydrogen generator with nine plates of stainless steel was fabricated. The hydrogen generator is capable of producing desirable quantities of hydrogen. The mass flow rate of the hydrogen was computed based on the current supplied. A rechargeable battery was chosen due to long life span and low maintenance. Apart from that, due to its desirable light weight properties, the hydrogen consumption of the bicycle is reduced. A brushless electric motor providing 200 Watt power to drive the bicycle was fitted. The maximum weight that the bicyle is able to withstand is around 60 kg, while the maximum speed attained is 25 km/hr under such weight considered.